Letter - Trades Union Congress; Picard, M. R.
021-0087-001 MUSEUM 8245. 44, GORDON SQUARE, W.C.1. 1st March 1937 The Organising Secretary, International Conference of Trade Unions, Transport House, Smith Square, S.W.1 Dear Sir, I write to offer you my services as interpreter for the conference which will take place on the 10th and 11th of this month. I would mention that I have interpreted at the following conferences : International Consulting Committee on Radio-Communications, Lisbon, 1934 International Air Traffic Association, Madrid, 1935 Bureau International de la Paix, Brussels, 1935 International Parliamentary Commercial Conference, London, 1935 Yours faithfully, M.P. Ricard 292/946/21/87